KAJIAN STILISTIKA PADA YOUTUBE “ATAP NEGERI PAPUA TENGAH” - Faqih Fathkurullah Arrahman; Sugit Zulianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is inspired by the phenomenon of esthetic and captivating language use in audiovisual content, particularly in the works of Fiersa Besari, which are often enjoyed visually without a deep understanding of their linguistic construction. Therefore, this research aims to describe the use of diction, language style, and imagery in the oral narration of the YouTube video "Ekspedisi Atap Negeri" Central Papua. The approach used is qualitative descriptive. Data were collected thru note-taking techniques on five episodes of the Puncak Jaya Mountain climbing series videos, selected using purposive sampling techniques, and validated with theoretical triangulation. The research findings revealed 176 diction data consisting of five types, with a dominance of foreign diction at 76.14%. Additionally, 74 data from nine types of stylistic devices were found, predominantly assonance, which is the repetition of words or vowel sounds in adjacent words or sentences, at a rate of 28.38%. The study also identified 24 data from five types of imagery, predominantly visual imagery at 41.67%. Based on these findings, it can be concluded that the oral narration in this video is functionally constructed using rich and poetic linguistic elements to deeply engage the audience's emotions. Theoretically, this research enriches the study of stylistics in digital literature. Practically, this digital literary work has proven to be relevant and highly effective as an innovative alternative learning medium for poetry text material for students, as well as bridging literary learning with contemporary digital literacy.